Potential role of CC chemokine receptor 6 in prediction of late‐onset cytomegalovirus infection following solid organ transplant. (22nd April 2015) - Camargo, Jose F.; Resende, Mariangela R.; Zamel, Ricardo; Klement, William; Bhimji, Alyajahan; Huibner, Sanja; Kumar, Deepali; Humar, Atul; Jurisica, Igor; Keshavjee, Shaf; Kaul, Rupert; Husain, Shahid
Abstract CCR6 is a chemokine receptor involved in homing memory T cells, particularly Th17 cells, to sites of mucosal inflammation. Despite the critical role of memory T cells in long‐term protective immunity against cytomegalovirus (CMV), a virus that reactivates at multiple mucosal sites, the ability of CCR6 or other Th17 marker expression to predict CMV reactivation following transplantation is not clear. Using 11‐color flow cytometry, in this prospective single‐center pilot study, we measured the expression of CCR6 and other markers of T‐cell function in peripheral blood samples obtained from 21 SOT recipients at the time of discontinuation of anti‐CMV prophylaxis. CMV viremia was monitored on a monthly basis after discontinuation of prophylaxis. Eleven patients (52%) developed CMV viremia during the six‐month follow‐up period. Late‐onset CMV infection was preceded by an immune phenotype characterized by increased CCR6 expression on bulk CD4+ T cells and a reduced number of circulating CMV IE‐1‐specific Th1 (CD4+ IFN‐γ+) cells. Among the markers evaluated, CCR6 was the best single predictor of late‐onset CMV infection. Our results suggest that CCR6 expression at the time of discontinuation of antiviral prophylaxis might be a useful predictor of late‐onset CMV reactivation and provide the basis for future larger prospective studies.